Problem analysis and solution for performance improvement in multi-hop ad hoc network
<span lang="EN-US" style="color: black; font-family: "Times New Roman","serif"; font-size: 11pt; mso-ansi-language: EN-US; mso-fareast-font-family: "Times New Roman"; mso-fareast-language: VI; mso-bidi-language: AR-SA;">.